Pengaruh Pengaruh Online Customer Review, City Image dan Perceived Price Terhadap Purchase Intention Pada Bolu Meranti - Putri, Utami Astria; Simanjuntak, Demak Claudia Yosephine; Sitorus, Daniel Ronaldo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The aim of this research is to analyze the influence of online customer reviews, urban landscape and price image on purchasing intentions of Bolu Meranti, Medan City. The aim of the research is to determine the relationship between variables and the influence of the independent variable and the dependent variable. The type of research used is a quantitative method. Data collection methods in the form of observation and questionnaires were used in this research. This survey covers all Bolu Meranti consumers whose numbers are unknown. The research sample was determined using the Coachran formula, totaling 96. SPSS version 24.0 was used for data processing in this research. Data analysis uses validity, reliability, classical hypothesis testing using normality test, multicollinearity test, heteroscedasticity test, linearity test, multiple linearity test. Next, the F test, t test and coefficient of determination test were carried out. The research results show that online customer reviews, city image and price perceptions simultaneously and partially influence purchase intentions for Bolu Merant in Medan.